Incorporating Cultural Exposure into Teaching Practices: Native Speaker Teacher vs Indonesian EFL Teacher - Rima Purwita Sari (Lingua Pedagogia, 2020)
As English language teacher, both Native English Speaker Teacher (NEST) and Indonesian EFL Teacher own professional competence as well their perception, assumption, beliefs and values that are shaped by their social and cultural interaction. They bring with them their personal and professional attributes into the classroom. As language and cultural aspects are interrelated, particularly since English is now a lingua franca, thus exploring how the different professional and personal background of English language teachers relates to their teaching becomes essential. The purpose of this study is to examine how teachers’ cultural exposure of the target language is incorporated and affects their teaching.  This study is qualitative in nature, aiming to describe how the cultural exposures of three different types of teachers are reflected in their teaching practices. Data collection is done through semi-structured interview, class observation and document analysis. The finding shows that teacher’s cultural exposure affects their teaching philosophy and attitude considerably large, particularly in their perspective towards student-teacher rapport. The incorporation of the cultural exposure is done through content of teaching materials and instruction in the classroom. The three types of teacher demonstrate a similar approach and methods when teaching the language, despite the differences in their cultural exposure of the target language.